UV absorbers

By combining ferulic acid with a water-insoluble cyclodextrin polymer, the UV absorption capacity across the 250-375 nm range is enhanced, addressing the limitations of existing ultraviolet absorbers in maintaining effective UV protection in various solution types.

JP7671459B2Active Publication Date: 2025-05-02AOMORI PREFECTURAL IND TECH RES CENT
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2021053233
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-26
Publication Date
2025-05-02
Estimated Expiration
2041-03-26

AI Technical Summary

Technical Problem

Existing ultraviolet absorbers, particularly those containing ferulic acid, face challenges in maintaining high UV absorption capacity across the entire UV-A and UV-C wavelength range and in aqueous or oily solutions where ferulic acid is insoluble or poorly soluble.

Method used

A water-insoluble cyclodextrin polymer is used in conjunction with ferulic acid to enhance UV absorption capabilities across the 250-375 nm wavelength range, even when added to aqueous or oily solutions where ferulic acid is not soluble.

Benefits of technology

The combination of ferulic acid with a water-insoluble cyclodextrin polymer significantly enhances UV absorption in the 250-375 nm range, ensuring effective protection against UV rays in various solution types.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007671459000004
    Figure 0007671459000004
  • Figure 0007671459000005
    Figure 0007671459000005
  • Figure 0007671459000006
    Figure 0007671459000006
Patent Text Reader

Abstract

To provide an ultraviolet absorber that has excellent ultraviolet absorbing ability in an ultraviolet wavelength range of 250-375 nm and has excellent ultraviolet absorbing ability for ultraviolet rays of a wavelength of 250-375 nm even when added to an aqueous solution, an oily substance, and the like in which ferulic acid is insoluble or difficult to dissolve.SOLUTION: By making ferulic acid adsorbed by a cyclodextrin polymer obtained by crosslinking cyclodextrin with an epoxy-based compound, there can be obtained a material that shows high ultraviolet absorbing ability for ultraviolet rays of a wavelength of 250-375 nm and has excellent ultraviolet absorbing ability for ultraviolet rays of a wavelength of 250-375 nm even when added to an aqueous solution, an oily substance, and the like in which ferulic acid is insoluble or difficult to dissolve.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an ultraviolet absorbing technology using ferulic acid in the ultraviolet absorbing range of wavelengths from 250 to 375 nm, 375 The present invention relates to an ultraviolet absorber that has high ultraviolet absorption ability over the entire ultraviolet wavelength range of 100 nm and that can be easily dispersed in aqueous solutions in which ferulic acid is insoluble or poorly soluble, and in liquid paraffinic and olefinic hydrocarbons. [Background technology]

[0002] The Japan Meteorological Agency classifies ultraviolet rays into three categories: UV-A with wavelengths of 315-400 nm, UV-B with wavelengths of 280-315 nm, and UV-C with wavelengths of 100-280 nm. UV-A accelerates skin aging and causes wrinkles and sagging, UV-B causes age spots, skin cancer, cataracts, and immunosuppression, and UV-C is the most harmful of the three categories of ultraviolet rays to living things and substances. Everyday, we are exposed to UV-A and UV-B as ultraviolet rays derived from solar radiation from the sun. It is said that UV-C derived from solar radiation from the sun is almost entirely absorbed by the stratosphere, ozone layer, and oxygen, and does not reach the ground, so we are not exposed to it. However, there are concerns that UV-C will reach the ground due to the decrease in absorption of UV-C caused by the destruction of the ozone layer, and in addition, devices that irradiate ultraviolet rays with wavelengths of around 254 nm to inactivate bacteria and viruses are commercially available and are used around us.

[0003] Ferulic acid is a substance found in plants such as rice, wheat, rye, barley, and apples. It has antioxidant, antibacterial, and anti-inflammatory properties, as well as ultraviolet absorbing properties. It is therefore registered on the positive list for cosmetics and is used in cosmetics such as sunscreen creams to prevent ultraviolet rays from sunlight from reaching the skin.

[0004] Cosmetics containing added ferulic acid have a high absorption capacity in the UV-B wavelength range, but the absorption capacity of ultraviolet light at each wavelength drops significantly as the UV-A wavelength range moves from 315 to 375 nm and as the UV-C wavelength range moves from 280 to 255 nm. Furthermore, when ferulic acid is insoluble or poorly soluble in aqueous solutions or oily substances, the ferulic acid does not disperse in the aqueous solution or oily substance, resulting in low absorption of ultraviolet light.

[0005] Patent Documents 1 and 2 disclose an inclusion compound in which ferulic acid is included in cyclodextrin, a cyclic oligosaccharide (hereinafter referred to as "CyD-FA inclusion compound"), as a material for using ferulic acid in cosmetics, etc. Patent Document 3 discloses an example of a cosmetic containing, as an active ingredient, an inclusion compound of a water-insoluble cyclodextrin polymer and γ-oryzanol.

[0006] The CyD-FA inclusion compounds disclosed in Patent Documents 1 and 2 do not disclose or suggest the problem of "the remarkable decrease in the ability to absorb ultraviolet light at each wavelength from 315 to 375 nm in the UV-A wavelength range and from 280 to 255 nm in the UV-C wavelength range" or the problem of "the decrease in ultraviolet light absorption in materials to which ferulic acid is added to aqueous solutions, oily substances, etc.", and do not solve these problems. Patent Document 3 discloses a cosmetic containing an oily component to which a water-insoluble cyclodextrin polymer is added as a scrubbing agent, and exemplifies γ-oryzanol, which has ferulic acid as part of its chemical structure, as an example of an oily component, but does not disclose or suggest the problem of "the remarkable decrease in the ability to absorb ultraviolet light at each wavelength from 315 to 375 nm in the UV-A wavelength range and from 280 to 255 nm in the UV-C wavelength range" or the problem of "the decrease in ultraviolet light absorption in materials to which ferulic acid is added to aqueous solutions, oily substances, etc.", and does not solve these problems. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] Patent Application Publication No. 5-47 [Patent Document 2] Patent application 2001-237836 [Patent Document 3] Patent Application No. 3-42647 Summary of the Invention [Problem to be solved by the invention]

[0008] Therefore, an object of the present invention is to provide an ultraviolet absorber that has excellent ultraviolet absorbing ability in the ultraviolet wavelength range of 250 to 375 nm, and that exhibits excellent ultraviolet absorbing ability for ultraviolet rays with wavelengths of 250 to 375 nm even when added to aqueous solutions or oily substances in which ferulic acid is insoluble or poorly soluble. [Means for solving the problem]

[0009] As a result of intensive research to solve the above problems, the inventors discovered that a water-insoluble cyclodextrin polymer is brought into contact with ferulic acid to form a composite agent of the water-insoluble cyclodextrin polymer and ferulic acid, which has high ultraviolet absorbing ability for ultraviolet rays with wavelengths of 250 to 375 nm, and thus arrived at the present invention. That is, the invention claimed in this application as a means for solving the above problems, or at least the invention disclosed therein, is as follows.

[0010] (1) An ultraviolet absorber consisting of water-insoluble cyclodextrin polymer and ferulic acid. (2) A method for producing an ultraviolet absorber, comprising contacting a water-insoluble cyclodextrin polymer with ferulic acid by adding ferulic acid dissolved in a solvent that is compatible with water and dissolves ferulic acid to water in which the water-insoluble cyclodextrin polymer is dispersed, and then separating the water-insoluble cyclodextrin polymer from the solution. Effect of the Invention

[0011] Since the ultraviolet absorbent and the method for producing the same of the present invention are configured as described above, by adsorbing ferulic acid, which is sold as a cosmetic ingredient, to a water-insoluble cyclodextrin polymer produced using readily available cyclodextrin and a crosslinking agent such as an epoxy compound, the ultraviolet absorbent can have an enhanced ability to absorb ultraviolet light with a wavelength of 250 to 375 nm. Furthermore, even when added to an aqueous solution or oily substance in which ferulic acid is not soluble, the ultraviolet absorbent can exhibit excellent ultraviolet absorbency for ultraviolet light with a wavelength of 250 to 375 nm.

[0012] The epoxy compound of the present invention refers to an organic compound having an epoxy ring in the intramolecular skeleton, and examples thereof include epichlorohydrin, ethylene glycol diglycidyl ether, and butanediol diglycidyl ether.

[0013] Furthermore, in the present invention, adsorption refers to any of the following states: a ferulic acid molecule or a part of the intramolecular structure of ferulic acid is included in the internal molecular space of the cyclodextrin constituting the water-insoluble epoxy compound cross-linked cyclodextrin polymer, enters the space surrounded by the cyclodextrin, or is fixed to the surface of the water-insoluble epoxy compound cyclodextrin polymer by hydrogen bonding, van der Waals forces, or the like. [Brief description of the drawings]

[0014] [Figure 1] 1 shows ultraviolet absorption spectra of a W-β-FA mixed solution, a W-β-FHA mixed solution, and a ferulic acid mixed solution (Example 1). [Diagram 2] 1 is a microscopic image of a W-β-FA mixed solution (Example 1). [Diagram 3] 1 is a microscopic image of a ferulic acid mixture solution (Example 1). [Figure 4] 1 shows ultraviolet absorption spectra of a W-β-FA mixed solution, a D-β-FA mixed solution, a W-β-CFA mixed solution, and a D-β-CFA mixed solution (Example 2). [Diagram 5]1 shows ultraviolet absorption spectra of a W-β-FA mixed solution, a W-α-FA mixed solution, a W-γ-FA mixed solution, and a ferulic acid mixed solution (Example 3). [Figure 6] 1 shows ultraviolet absorption spectra of a D-3-FA mixed solution, a W-β-FA mixed solution, a W-α-FA mixed solution, and a W-α-FA mixed solution (Example 4). [Figure 7] 1 shows ultraviolet absorption spectra of a mixed solution of D-β-FP solution, D-α-FP solution, D-γ-FP solution, and ferulic acid-P solution (Example 5). [Figure 8] 1 is a microscopic image of D-β-FP solution (Example 5). [Figure 9] 1 is a microscopic image of a ferulic acid-P liquid mixed solution (Example 5). [Figure 10] FIG. 6 is a graph showing curves of corrected values ​​and wavelengths for a W-β-FA mixed solution, a D-β-FA mixed solution, a W-β-CFA mixed solution, a D-β-CFA mixed solution, and a ferulic acid mixed solution (Example 6). [Figure 11] FIG. 6 is a graph showing the curves of the corrected values ​​and wavelengths for a W-α-FA mixed solution, a W-γ-FA mixed solution, and a ferulic acid mixed solution (Example 6). [Figure 12] FIG. 6 is a graph showing curves of corrected values ​​and wavelengths for D-β-FP solution, D-α-FP solution, D-γ-FP solution, and a mixed solution of ferulic acid (Example 6). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] The water-insoluble cyclodextrin polymer (hereinafter referred to as "CDP") used in the ultraviolet absorbent of this embodiment can be produced by, for example, crosslinking cyclodextrin with an epoxy compound or the like to obtain a suitable particle size, or crosslinking cyclodextrin with an epoxy compound or the like to obtain a block, and then pulverizing the block to a suitable particle size in a wet state or in a dry state after drying. The CDP used in the operation of adsorbing ferulic acid to CDP may be in a wet state or a dry state, and the ferulic acid-adsorbed CDP after the operation of adsorbing ferulic acid to CDP may be in a wet state or may be in a dry state by drying.

[0016] The CDP constituting the ferulic acid adsorbed CDP may be any one of the following: a water-insoluble polymer obtained by crosslinking α-cyclodextrin with an epoxy compound (hereinafter referred to as "α-CDP"), a water-insoluble polymer obtained by crosslinking β-cyclodextrin with an epoxy compound (hereinafter referred to as "β-CDP"), and a water-insoluble polymer obtained by crosslinking γ-cyclodextrin with an epoxy compound (hereinafter referred to as "γ-CDP"). It may also be a mixture of two or three of α-CDP, β-CDP, and γ-CDP in any ratio. In addition, a water-insoluble polymer obtained by crosslinking a cyclodextrin mixed with two or three types of cyclodextrins among α-, β-, and γ-cyclodextrin with an epoxy compound may also be used as the CDP constituting the ferulic acid adsorbed CDP.

[0017] A ferulic acid-adsorbed CDP composed of two or more types of CDP may be prepared by mixing two or more types of CDP and then adsorbing ferulic acid thereon, or each ferulic acid-adsorbed CDP may be mixed.

[0018] The drying process may be carried out in any of an atmosphere including an air atmosphere, a vacuum atmosphere in which gas is sucked in by a pump such as a rotary pump, an inert gas atmosphere such as helium gas, neon gas, argon gas, krypton gas, xenon gas, and nitrogen gas, and a carbon dioxide atmosphere. EXAMPLES

[0019] Next, examples of the present invention will be described. The preparation examples shown below are illustrative of the ultraviolet absorbent for embodying the technical idea of ​​the present invention and the preparation method of the water-insoluble cyclodextrin polymer used in the ultraviolet absorbent, and do not limit the technical idea of ​​the present invention to the following. In addition, in the following Examples 1 to 6, the ultraviolet absorption behavior of the water-insoluble cyclodextrin polymer adsorbed with ferulic acid using a specific aqueous solution or organic compound as a dispersion medium is illustrated as an example in order to embody the technical idea of ​​the present invention, but the dispersion medium of the water-insoluble cyclodextrin polymer adsorbed with ferulic acid, which is the ultraviolet absorbent of the present invention, only needs to be liquid during dispersion treatment, and is not limited to the following. The technical idea of ​​the present invention can be variously modified within the technical scope defined by the claims described in the claims. Hereinafter, the water-insoluble cyclodextrin polymer is also referred to as cyclodextrin polymer.

[0020] In the examples of the present invention, ferulic acid manufactured by Tsuno Rice Fine Chemicals Co., Ltd. was used.

[0021] Various tests and calculations of values ​​in the examples were carried out in the following manner.

[0022] (Calculation of the amount of ferulic acid per 1 g of water-insoluble cyclodextrin polymer in terms of dry matter) The amount of ferulic acid per 1 g of water-insoluble cyclodextrin polymer (hereinafter referred to as "CDP-F amount") [mg / g-DRY] was calculated by measuring the absorbance at 315 nm of the supernatant after centrifuging a solution containing water-insoluble cyclodextrin polymer, water, and an ethanol solution of ferulic acid using an ultraviolet-visible near-infrared spectrophotometer (V-770, JASCO), substituting the absorbance at 315 nm of the obtained supernatant into a calibration curve of absorbance at 315 nm and ferulic acid concentration prepared in advance using a standard substance, determining the ferulic acid concentration C1 [mg / mL] of the supernatant, and substituting C1 into formula 1. Unless otherwise specified, V is 20 mL, which is the total amount of water and ethanol solution of ferulic acid used.

[0023] (Formula 1) CDP-F amount = (59.83-C1×V) / 0.75...Equation 1

[0024] (UV absorption spectrum measurement) The ultraviolet absorption spectrum was obtained by applying a sample containing ferulic acid-adsorbed water-insoluble cyclodextrin polymer, setting a covered quartz cell (Type20 / O / Q / 0.02, Sterner) with an optical path length of 20 μm on the sample fixing part for diffuse transmittance measurement of an integrating sphere (ISN-923, JASCO) attached to an ultraviolet / visible / near infrared spectrophotometer (V-770, JASCO), and measuring the wavelength range of 400-200 nm with a wavelength interval of 1 nm while changing the measurement wavelength from long wavelength to short wavelength. Note that the absorbance at 400 nm was set to zero before the measurement.

[0025] The absorbance is a value calculated using Equation 2, where I0 is the intensity of incident light and I is the intensity of transmitted light.

[0026] (Formula 2) Absorbance=-log 10 (I0 / I) Equation 2

[0027] (Microscopic image acquisition) The microscopic images were taken by observing the sample placed in a quartz cell with an optical path length of 20 μm, which was used for measuring the ultraviolet absorption spectrum, using a digital microscope (HRX-01, Hirox Corporation).

[0028] (moisture content) The moisture content is the value calculated by substituting M1 [g], the weight of an analytical sample for moisture content analysis, after heat treatment at 50°C for 12 hours at 1 hectopascal or less, into Equation 3.

[0029] (Formula 3) Moisture content [mass%]=((M-M1) / M1)×100...Equation 3

[0030] (Volume Moment Mean Diameter) The volume moment mean diameter was measured by using a laser diffraction particle size distribution analyzer (Mastersizer 3000, Malvern Co.) to measure water-insoluble cyclodextrin polymer using water as the dispersion medium, and analyzed using the software provided with the device.

[0031] <Preparation of Granular β-Cyclodextrin Polymer> After dissolving 150.0 g of β-cyclodextrin in an aqueous sodium hydroxide solution (NaOH 200.0 g / H2O 500.0 g), 150.0 g of amorphous silicic acid was added, and the resulting solution was placed in a 1 L round-bottomed separable flask (hereinafter referred to as "separable flask") with a three-necked separable cover, which was placed in a cooling liquid at -5°C, and the solution in the separable flask was stirred at 200 rpm with a stirring rod with a 90 mm wide round-shaped stirring blade made of fluororesin. Next, the solution in the separable flask was cooled to 0°C, and then 114.0 g of epichlorohydrin was placed in the separable flask, and the solution in the separable flask was cooled and stirred with a stirring rod at 200 rpm while placed in a cooling liquid at -5°C for 240 hours. The solution in the separable flask was placed in a 3L glass beaker containing 2000g of water, stirred with a glass rod until the white solid was dispersed throughout the water, allowed to stand to allow the white solid to precipitate, and then the supernatant aqueous solution was removed.Furthermore, 2000g of water was placed in the 3L glass beaker containing the white solid, stirred with a glass rod, allowed to stand to allow the white solid to precipitate, and then the supernatant aqueous solution was removed, until the pH of the supernatant aqueous solution became neutral, yielding a wet white granular β-cyclodextrin polymer (hereinafter referred to as "W-β-CDP") with a water content of 70.6% and a volume moment average diameter of 13.2μm.

[0032] <Preparation of Granular α-Cyclodextrin Polymer> In the same manner as in the preparation of granular β-cyclodextrin polymer, 128.7 g of α-cyclodextrin was dissolved in an aqueous sodium hydroxide solution (NaOH 200.0 g / H2O 500.0 g), and then 150.0 g of amorphous silicic acid was added. The separable flask containing the dissolved solution was placed in a cooling liquid at -5°C, and the solution in the separable flask was stirred at 200 rpm with a stirring rod with a 90 mm wide round-shaped stirring blade made of fluororesin. Next, the solution in the separable flask was cooled to 0°C, and then 114.0 g of epichlorohydrin was placed in the separable flask, and the solution in the separable flask was cooled and stirred with a stirring rod at 200 rpm while placed in a cooling liquid at -5°C for 240 hours. The solution in the separable flask was placed in a 3L glass beaker containing 2000g of water, stirred with a glass rod until the white solid was dispersed throughout the water, allowed to stand to allow the white solid to precipitate, and then the supernatant aqueous solution was removed.Furthermore, 2000g of water was placed in the 3L glass beaker containing the white solid, stirred with a glass rod, allowed to stand to allow the white solid to precipitate, and then the supernatant aqueous solution was removed, until the pH of the supernatant aqueous solution became neutral, yielding a wet white granular α-cyclodextrin polymer (hereinafter referred to as "W-α-CDP") with a water content of 70.1% and a volume moment mean diameter of 9.0μm.

[0033] <Preparation of Granular γ-Cyclodextrin Polymer> In the same manner as in the preparation of granular β-cyclodextrin polymer, 171.5 g of γ-cyclodextrin was dissolved in an aqueous sodium hydroxide solution (NaOH 200.0 g / H2O 500.0 g), and then 150.0 g of amorphous silicic acid was added. The separable flask containing the dissolved solution was placed in a cooling liquid at -5°C, and the solution in the separable flask was stirred at 200 rpm with a stirring rod with a 90 mm wide round-shaped stirring blade made of fluororesin. Next, the solution in the separable flask was cooled to 0°C, and then 114.0 g of epichlorohydrin was placed in the separable flask, and the solution in the separable flask was cooled and stirred with a stirring rod at 200 rpm while placed in a cooling liquid at -5°C for 240 hours. The solution in the separable flask was placed in a 3L glass beaker containing 2000g of water, stirred with a glass rod until the white solid was dispersed throughout the water, allowed to stand to allow the white solid to precipitate, and then the supernatant aqueous solution was removed.Furthermore, 2000g of water was placed in the 3L glass beaker containing the white solid, stirred with a glass rod, allowed to stand to allow the white solid to precipitate, and then the supernatant aqueous solution was removed, until the pH of the supernatant aqueous solution became neutral, yielding a wet white granular γ-cyclodextrin polymer (hereinafter referred to as "W-γ-CDP") with a water content of 79.6% and a volume moment mean diameter of 9.0μm.

[0034] <Preparation of finely ground β-cyclodextrin polymer> A separable flask containing a solution of 150.0 g of β-cyclodextrin dissolved in sodium hydroxide solution (NaOH 63.0 g / H2O 150.0 g) was placed in a thermostatic liquid at 60°C, and the solution in the separable flask was stirred at 200 rpm with a stirring rod with a 90 mm wide round-shaped stirring blade made of fluororesin. Next, the solution in the separable flask was cooled to 60°C, and then 114.0 g of epichlorohydrin was placed in the separable flask, and stirring with a stirring rod at 200 rpm was continued for 2 hours while the solution was in a thermostatic liquid at 60°C. The precipitate was filtered, and further filtered and washed until the washing liquid became neutral, and then coarsely crushed in an alumina mortar. The coarsely ground precipitate was ground in water using a homogenizer (PT10-35 with PTA10S attached, KINEMATICA), and then allowed to stand for 10 minutes. The supernatant was placed in a 500 mL plastic bottle for centrifugation, and centrifuged at 24°C, 12,000 rpm, and 10 minutes using a high-speed refrigerated centrifuge (CR22GIII, Hitachi Koki Co., Ltd.). The precipitated white solid was collected, and a wet white finely ground β-cyclodextrin polymer (hereinafter referred to as "W-β-CDP-C") with a water content of 73.4% and a volume moment average diameter of 18.9 μm was obtained.

[0035] <Preparation of Water-Insoluble Cyclodextrin Polymer-Ferulic Acid Complex> In a 40 mL centrifuge container with a lid, 19 mL of water and 0.75 g of water-insoluble cyclodextrin polymer in dry matter equivalent were placed, followed by 1 mL of ethanol solution containing 2.992 g of ferulic acid in 50 mL of ethanol, which was shaken and stirred, then the container was covered and left to stand at room temperature for 12 hours. Next, using a high-speed refrigerated centrifuge (CR22GIII type, Hitachi Koki Co., Ltd.), centrifugation was performed at 24°C, 15,000 rpm, 20 minutes, and the precipitated white solid was collected to obtain a water-insoluble cyclodextrin polymer-ferulic acid complex. The table shows the water-insoluble cyclodextrin polymer-ferulic acid complex prepared and its preparation conditions, the amount of ferulic acid per 1 g of water-insoluble cyclodextrin polymer in dry matter equivalent, and the water content. rate showed.

[0036] [Table 1]

[0037] In addition, the wet water-insoluble cyclodextrin polymer was used as the raw material for preparing the water-insoluble cyclodextrin polymer-ferulic acid complex. Since the difference in water content between the prepared water-insoluble cyclodextrin polymer-ferulic acid complex and the water-insoluble cyclodextrin polymer used was small, the amount of ferulic acid per gram of the water-insoluble cyclodextrin polymer in terms of dry matter was calculated without correcting the supernatant after centrifugation for concentration or dilution by water contained in the water-insoluble cyclodextrin polymer.

[0038] <Preparation of ferulic acid-rich β-cyclodextrin polymer-ferulic acid complex> In a 40mL centrifuge container with a lid, 17mL of water and 0.75g of W-β-CDP in terms of dry matter were placed, followed by 3mL of ethanol solution containing 2.992g of ferulic acid in 50mL of ethanol, followed by shaking and stirring, then the container was covered and left to stand at room temperature for 12 hours. Next, the container was centrifuged at 24℃, 15000rpm, and 20 minutes using a high-speed refrigerated centrifuge (CR22GIII type, Hitachi Koki Co., Ltd.), and the precipitated white solid was collected to obtain a highly ferulic acid-adsorbed β-cyclodextrin polymer-ferulic acid composite (hereinafter referred to as "W-β-FH") with a water content of 70.5% and a ferulic acid content of 206.3mg / g-DRY per 1g of water-insoluble cyclodextrin polymer in terms of dry matter.

[0039] In addition, moist β-cyclodextrin polymer was used as the raw material for preparing the high ferulic acid-adsorbed β-cyclodextrin polymer-ferulic acid complex. Since the difference in water content between the prepared high ferulic acid-adsorbed β-cyclodextrin polymer-ferulic acid complex and the W-β-CDP used was small, the amount of ferulic acid per 1 g of the water-insoluble cyclodextrin polymer in terms of dry matter was not corrected for the concentration or dilution of the supernatant after centrifugation by the water contained in W-β-CDP when calculating the amount of ferulic acid per 1 g of the water-insoluble cyclodextrin polymer in terms of dry matter.

[0040] <Preparation of dry β-cyclodextrin polymer-ferulic acid complex> In a 40mL container with a lid for centrifugation, 19mL of water and 0.75g of dried W-β-CDP dried under vacuum at 50℃ for 12 hours were placed, followed by 1mL of ethanol solution containing 2.992g of ferulic acid in 50mL of ethanol, followed by shaking and stirring, then the container was covered and left to stand at room temperature for 12 hours. Next, the container was centrifuged at 24℃, 15000rpm, 20 minutes using a high-speed refrigerated centrifuge (CR22GIII type, Hitachi Koki Co., Ltd.), and the precipitated white solid was collected to obtain a ferulic acid adsorbed dried β-cyclodextrin polymer-ferulic acid complex (hereinafter referred to as "D-β-F") with a water content of 70.3% and a ferulic acid amount of 65.3mg / g-DRY per 1g of water-insoluble cyclodextrin polymer in terms of dry matter.

[0041] In addition, the same procedure for preparing D-β-F was performed using W-β-CDP-C instead of W-β-CDP, and a ferulic acid-adsorbed, dried, finely ground β-cyclodextrin polymer-ferulic acid composite (hereinafter referred to as "D-β-CF") was obtained, with a water content of 73.5% and an amount of ferulic acid per gram of water-insoluble cyclodextrin polymer equivalent to 65.4 mg / g-DRY.

[0042] In addition, in the preparation of both D-β-F and D-β-CF, dried β-cyclodextrin polymer was used as the raw material, and D-β-F contained 1.8 g of water after preparation, and D-β-CF contained 2.1 g of water. Therefore, when calculating the amount of ferulic acid per 1 g of the water-insoluble cyclodextrin polymer of D-β-F and D-β-CF, the amount of water contained in D-β-F and D-β-CF was used to correct for the concentration of the supernatant after centrifugation. In other words, the calculation was performed by setting V in Equation 1 to 18.2 mL for D-β-F and 17.9 mL for D-β-CF.

[0043] (Preparation of a mixed solution of water-insoluble cyclodextrin polymer-ferulic acid complex and sodium alginate aqueous solution) In an alumina mortar, 1000μL of a water-insoluble cyclodextrin polymer-ferulic acid complex (hereinafter referred to as "CDP-ferulic acid complex") and 1.0g of sodium alginate dissolved in 50mL of water were placed, and the mixture was stirred for 30 seconds with a pestle to prepare a mixture of CDP-ferulic acid complex and sodium alginate aqueous solution (hereinafter referred to as "CDP-F-Aaq mixture"). In addition, a mixture of ferulic acid and sodium alginate aqueous solution (hereinafter referred to as "ferulic acid mixture") was prepared by the same procedure using ferulic acid instead of CDP-ferulic acid complex. Table 2 shows each CDP-F-Aaq prepared, its preparation conditions, and the calculated amount of ferulic acid contained in 1mL of CDP-F-Aaq mixture (hereinafter referred to as "1mL_WF amount"). The CDP-ferulic acid complexes used were W-β-F, W-β-FH, D-β-F, W-β-CF, D-β-CF, W-α-F, and W-γ-F, and the prepared CDP-F-Aaq were respectively referred to as W-β-FA mixed solution, W-β-FHA mixed solution, D-β-FA mixed solution, W-β-CFA mixed solution, D-β-CFA mixed solution, W-α-FA mixed solution, and W-γ-FA mixed solution.

[0044] (Table 2) TIFF0007671459000002.tif45160

[0045] The 1mL_WF amount [mg / mL] is the value calculated using Equation 4 when the wet weight of the CDP-ferulic acid complex used, its water content, and the amount of ferulic acid per 1g of the water-insoluble cyclodextrin polymer in dry weight equivalent are Ww [g], Mc [%], and Fc [mg / g-DRY], respectively, and the density of the cyclodextrin polymer in the dry state is 1.3 [g / mL].

[0046] (Formula 4) 1mL_WF amount=(( Ww ×(1-Mc / 100))×Fc) / (1+ (Ww×(1-Mc / 100)) / 1.3)...Equation 4

[0047] (Preparation of a mixed solution of water-insoluble cyclodextrin polymer-ferulic acid complex and sodium alginate aqueous solution 2) In the same manner as in the preparation of the CDP-F-Aaq mixed solution, 51.3 mg, 50.7 mg, and 54.3 mg of W-β-F, W-α-F, and W-γ-F, which had been dried in a vacuum at 50°C for 12 hours, were placed in an alumina mortar, and 1000 μL of an aqueous solution of 1.0 g of sodium alginate dissolved in 50 mL of water was placed in the mortar, and the mixture was stirred for 30 seconds with a pestle to prepare a mixed solution of three types of CDP-ferulic acid complexes and an aqueous sodium alginate solution (hereinafter referred to as the "D-3-FA mixed solution"). The amount of ferulic acid contained in 1 mL of the D-3-FA mixed solution was calculated to be 9.71 mg / mL from the dry weights of W-β-F, W-α-F, and W-γ-F used and the amount of ferulic acid per 1 g of the water-insoluble cyclodextrin polymer in terms of dry matter.

[0048] (Preparation of a mixture of water-insoluble cyclodextrin polymer-ferulic acid complex and liquid paraffin) In the same manner as in the preparation of the CDP-F-Aaq mixed solution, a cyclodextrin polymer-ferulic acid complex (hereinafter referred to as "dried CDP-ferulic acid complex") dried for 12 hours at 50°C in a vacuum was placed in an alumina mortar and mixed with 1000 μL of liquid paraffin for 30 seconds with a pestle to prepare a mixed solution of the dried CDP-ferulic acid complex and liquid paraffin (hereinafter referred to as D-CDP-FP solution). In addition, a mixed solution of ferulic acid and liquid paraffin (hereinafter referred to as "ferulic acid-P solution") was prepared by the same procedure using ferulic acid instead of the dried CDP-ferulic acid complex. In addition, a mixed solution of W-β-F and liquid paraffin (hereinafter referred to as "W-β-FP solution") was prepared by the same procedure using 510.7 mg of W-β-F instead of the dried CDP-ferulic acid complex. The amount of ferulic acid contained in 1 mL of W-β-FP solution calculated is 9.15 mg / mL. Table 3 shows the prepared D-CDP-FP solution, its preparation conditions, and the amount of ferulic acid contained in 1 mL of D-CDP-FP solution calculated by calculation (hereinafter referred to as "1 mL_DF amount"). The CDP-ferulic acid complexes used were W-β-F, W-α-F, and W-γ-F, and the prepared D-CDP-FP solutions were respectively indicated as D-β-FP solution, D-α-FP solution, and D-γ-FP solution.

[0049] (Table 3) TIFF0007671459000003.tif27155

[0050] The 1mL_DF amount [mg / mL] is the value calculated using formula 5 when the dry weight of the dried CDP-ferulic acid complex and the amount of ferulic acid per 1g of the water-insoluble cyclodextrin polymer used are Wd [g] and Fc [mg / g-DRY], respectively, and the density of the cyclodextrin polymer in the dry state is 1.3 [g / mL].

[0051] (Formula 5) 1mL_DF amount=(Wd×Fc) / (1+Wd / 1.3)...Equation 5

[0052] <Example 1> The ultraviolet absorption spectra of the prepared W-β-FA mixed solution, W-β-FHA mixed solution, and the ferulic acid mixed solution as Comparative Example 1 were measured, and the results are shown in Figure 1. Figures 2 and 3 show microscope images of the W-β-FA mixed solution and the ferulic acid mixed solution at a magnification of 160 times.

[0053] Although the 1mL_WF volume of the W-β-FA mixed solution was smaller than that of the ferulic acid mixed solution, the W-β-FA mixed solution showed higher UV absorption capacity over the entire wavelength range of 250-375 nm. In addition, the absorption spectra of the W-β-FA mixed solution and the W-β-FHA mixed solution, which use the same water-insoluble cyclodextrin polymer and have a larger 1mL_WF volume than the W-β-FHA mixed solution, at wavelengths of 250-375 nm showed that the W-β-FHA mixed solution showed higher absorption capacity, with the maximum absorption wavelengths of 316 nm and 315 nm, and the minimum absorption wavelengths of 264 nm and 262 nm, respectively, showing very similar UV absorption spectrum patterns. Microscope images showed that the W-β-FA mixed solution had cyclodextrin polymer dispersed throughout the solution, while the ferulic acid mixed solution did not show any dispersion of ferulic acid particles throughout the solution.

[0054] <Example 2> The ultraviolet absorption spectra of the prepared D-β-FA mixed solution, W-β-CFA mixed solution, and D-β-CFA mixed solution were measured, and the results are shown in Figure 4. The ultraviolet absorption spectrum of the W-β-FA mixed solution is the measurement data of Example 1.

[0055] The water-insoluble cyclodextrin polymer-ferulic acid complexes prepared using wet and dried microparticulate β-cyclodextrin polymer and wet and dried micropulverized β-cyclodextrin polymer were used as raw materials. The UV absorption spectra of W-β-FA mixed solution, D-β-FA mixed solution, W-β-CFA mixed solution, and D-β-CFA mixed solution, each with a 1mL WF content in the narrow range of 8.52-9.15mg / mL, showed maximum absorption wavelengths of 316nm, 316nm, 316nm, and 316nm, respectively, and minimum absorption wavelengths of 264nm, 264nm, 262nm, and 263nm, respectively, and showed very similar UV absorption spectral patterns.

[0056] <Example 3> The ultraviolet absorption spectra of the prepared W-α-FA mixed solution and W-γ-FA mixed solution were measured, and the results are shown in Figure 5. The ultraviolet absorption spectrum of the W-β-FA mixed solution is the measurement data of Example 1, and the ultraviolet absorption spectrum of the ferulic acid mixed solution of Example 1 is also shown as Comparative Example 2.

[0057] Although the 1 mL WF volume of the W-β-FA mixed solution, W-α-FA mixed solution, and W-γ-FA mixed solution was similar to or smaller than the 1 mL WF volume of the ferulic acid mixed solution, all of the W-β-FA mixed solution, W-α-FA mixed solution, and W-γ-FA mixed solution showed higher UV absorption ability than the ferulic acid mixed solution over the entire wavelength range of 250 to 375 nm. In addition, different cyclodextrins, namely β-cyclodextrin, α-cyclodextrin, and γ-cyclodextrin, were used as the raw material for the water-insoluble cyclodextrin polymer, and the UV absorption spectra of the W-β-FA mixed solution, W-α-FA mixed solution, and W-γ-FA mixed solution, whose 1 mL WF amount was in the range of 8.98 to 10.4 mg / mL, were respectively, with maximum absorption wavelengths of 316 nm, 327 nm, and 316 nm, and minimum absorption wavelengths of 264 nm, 267 nm, and 263 nm.The UV absorption spectrum patterns of the W-β-FA mixed solution and the W-γ-FA mixed solution were similar, but the W-α-FA mixed solution showed a different UV absorption spectrum pattern.

[0058] <Example 4> The ultraviolet absorption spectrum of the prepared D-3-FA mixed solution was measured, and the results are shown in Figure 6. The ultraviolet absorption spectrum of the W-β-FA mixed solution is the measurement data of Example 1, and the ultraviolet absorption spectra of the W-α-FA mixed solution and W-α-FA mixed solution are the measurement data of Example 3.

[0059] The total dry weight of W-β-F, W-α-F, and W-γ-F in the D-3-FA mixed solution was 156.3 mg, the dry equivalent weight of W-β-F in the W-β-FA mixed solution was 152.6 mg, the dry equivalent weight of W-α-F in the W-α-FA mixed solution was 152.7 mg, and the dry equivalent weight of W-α-F in the W-α-FA mixed solution was 151.7 mg, which are similar dry weights. The ultraviolet absorption spectrum of the D-3-FA mixed solution showed a pattern almost identical to the curve connecting the points of the average absorbance at each wavelength of the ultraviolet absorption spectrum of each of the W-β-FA mixed solution, W-β-FA mixed solution, and W-β-FA mixed solution.

[0060] <Example 5> The ultraviolet absorption spectra of the prepared D-β-FP solution, D-α-FP solution, and D-γ-FP solution, and the ferulic acid-P solution mixed solution as Comparative Example 3, were measured, and the results are shown in Figure 7. Figures 8 and 9 show microscope images of the D-β-FP solution and the ferulic acid-P solution at a magnification of 160 times.

[0061] In the entire wavelength range from 250 to 375 nm, ferulic acid-P solution showed a flat UV absorption spectrum with an absorbance of around 0, while D-β-FP solution, D-α-FP solution, and D-γ-FP solution all showed UV absorption spectra with an absorbance of 0.11 or higher. Microscope images showed that D-β-FP solution had a dispersed state of cyclodextrin polymer in the solution, while ferulic acid-P solution did not show a dispersed state of ferulic acid particles in the entire solution.

[0062] <Example 6> For the ultraviolet absorption spectra in the wavelength range of 250 to 375 nm of the W-β-FA mixed solution, D-β-FA mixed solution, W-β-CFA mixed solution, D-β-CFA mixed solution, W-α-FA mixed solution, W-γ-FA mixed solution, D-β-FP solution, D-α-FP solution, and D-γ-FP solution of Examples 1 to 3 and 5, the absorbance at the maximum absorption wavelength was set to 1, and the absorbance at other wavelengths was corrected. Figure 10 shows the curves of the correction values ​​vs. wavelength for the W-β-FA mixed solution, D-β-FA mixed solution, W-β-CFA mixed solution, and D-β-CFA mixed solution, Figure 11 shows the curves of the correction values ​​vs. wavelength for the W-α-FA mixed solution and W-γ-FA mixed solution, and Figure 12 shows the curves of the correction values ​​vs. wavelength for the D-β-FP solution, D-α-FP solution, and D-γ-FP solution. In all the figures, a curve of the correction value vs. wavelength for the ferulic acid mixed solution is shown as Comparative Example 3.

[0063] If the absorbance at the maximum absorption wavelength is Aλmax and the absorbance at other wavelengths is Aλ, the correction value for each wavelength is calculated using Equation 6.

[0064] (Formula 6) Correction value for each wavelength = Aλ × (1 / Aλmax) Equation 6

[0065] In the curves of the correction value vs. wavelength for all of the W-β-FA mixed solution, D-β-FA mixed solution, W-β-CFA mixed solution, D-β-CFA mixed solution, W-α-FA mixed solution, W-γ-FA mixed solution, D-β-FP solution, D-α-FP solution, and D-γ-FP solution, the drop in the curve from 315 to 375 nm and the drop in the curve from 280 to 250 nm were smaller than those for the ferulic acid mixed solution. In addition, the minimum values ​​of the curves of the correction value vs. wavelength for all of the W-β-FA mixed solution, D-β-FA mixed solution, W-β-CFA mixed solution, D-β-CFA mixed solution, W-α-FA mixed solution, W-γ-FA mixed solution, D-β-FP solution, D-α-FP solution, and D-γ-FP solution were smaller than those for the ferulic acid mixed solution. solution It was shown that the values ​​were greater than those of [Industrial Applicability]

[0066] According to the present invention, by adsorbing ferulic acid, which is sold as a cosmetic raw material, to a water-insoluble cyclodextrin polymer produced using readily available cyclodextrin and a crosslinking agent such as an epoxy compound, it is possible to enhance the absorption ability of ultraviolet rays with wavelengths of 250 to 375 nm, and even when added to an aqueous solution or oily substance in which ferulic acid is not soluble, it is possible to exhibit excellent ultraviolet absorption ability for ultraviolet rays with wavelengths of 250 to 375 nm. Therefore, this invention has high industrial applicability.

Claims

[Claim 1] An ultraviolet absorber consisting of an epoxy compound cross-linked water-insoluble cyclodextrin polymer and ferulic acid, which satisfies all of the following ABS values: 0.04 or more from 375 nm to 351 nm, 0.30 or more from 350 nm to 301 nm, and 0.25 or more from 300 nm to 250 nm. ABS value: A quartz cell with an optical path length of 20 μm coated with a liquid prepared by mixing an epoxy compound cross-linked water-insoluble cyclodextrin polymer-ferulic acid composite with an alginic acid aqueous solution or liquid paraffin so that the ferulic acid content is 9.46±0.94 mg / mL is set in the sample fixing section for diffuse transmittance measurement of an integrating sphere attached to an ultraviolet / visible / near-infrared spectrophotometer, and the absorbance value for each wavelength from 250 nm to 375 nm is measured with the absorbance at a wavelength of 400 nm set to zero.

Citation Information

Patent Citations

  • Waterproof camera and mount mechanism for interchangeable lens thereof

    JP1991042647A

  • Tea leaf water content measuring device

    JP1993000047A

  • Cosmetic

    JP1993105619A

  • New clathrate compound and use thereof

    JP1994199733A

  • Light-resistant plastic composition

    JP1995207063A